1974
DOI: 10.1037/h0081866
|View full text |Cite
|
Sign up to set email alerts
|

Solitary confinement of prisoners: An assessment of its effects on inmates' personal constructs and adrenocortical activity.

Abstract: The effects of 10 days prison solitary confinement on inmates' personal constructs and adrenocortical activity were examined. Eight Ss maintained their regular institutional routine. Eight Ss were placed for 10 days in solitary confinement. Personal construct (Repertory Grid Technique) rankings increased in stability for confined Ss as compared with non-confined Ss. This effect was more pronounced for "good" than for "bad" constructs for inmates independently rated as "simple" concept types. Adrenocortical fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Interestingly, Platt and Labate (1977) Buikhuisen & Hoekstra, 1974;Labate, 1977). There are, however, two studies similar in design and analysis with the present one and both (Gendreau et al, 1977; (Labate, 1977 Kouri, 1973;Bennett et al, 1971;Bennett, 1974aBennett, , 1974bCulbertson, 1975;Ecclestone et al, 1974;Eitzen, 1975;Gendreau, Burke, & Grant, 1978;Gendreau, Gibson, Surridge, & Hug, 1973;Gendreau, Hudson, &Marquis, 1976;Maskin, 1976;Reker & Meissner, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Platt and Labate (1977) Buikhuisen & Hoekstra, 1974;Labate, 1977). There are, however, two studies similar in design and analysis with the present one and both (Gendreau et al, 1977; (Labate, 1977 Kouri, 1973;Bennett et al, 1971;Bennett, 1974aBennett, , 1974bCulbertson, 1975;Ecclestone et al, 1974;Eitzen, 1975;Gendreau, Burke, & Grant, 1978;Gendreau, Gibson, Surridge, & Hug, 1973;Gendreau, Hudson, &Marquis, 1976;Maskin, 1976;Reker & Meissner, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Gendreau, Freedman, Wilde, and Scott (1972) found that inmates housed in segregation for 7 days exhibited decreased electroencephalogram (EEG) frequencies, while the EEG frequencies of general population inmates remained relatively stable. A study conducted by Ecclestone, Gendreau, and Knox (1974) revealed that prisoners placed in restrictive housing for 10 days commonly related “good constructs,” such as “honest,” “successful,” or “easy-going,” with their self-identity (p. 187). Ecclestone et al found that segregated inmates did not experience more or less of a stress response than general population inmates.…”
Section: Longitudinal Studies: the Impact Of Restrictive Housing On Pmentioning
confidence: 99%
“…Early studies by Gendreau and colleagues (Ecclestone et al, 1974;Gendreau & Bonta, 1984;Gendreau et al, 1968Gendreau et al, , 1970Gendreau et al, , 1972 used repeated measures experimental designs over periods of up to 10 days to explore the effects of segregation on psychological and physiological measures. Few negative impacts of segregation were found over these brief time periods.…”
Section: Longitudinal Designsmentioning
confidence: 99%
“…Several of these studies have been experimental in nature in that inmates who volunteer to be randomly assigned to either segregation or comparison conditions for a short period of time (e.g., Ecclestone, Gendreau, & Knox, 1974;Gendreau & Bonta, 1984;Gendreau, Freedman, Wilde, & Scott, 1968, 1972Gendreau, McLean, Parsons, Drake, & Ecclestone, 1970). These studies tend to show little impact of segregation on mental well-being but can be criticized for lacking ecological validity by using participants who volunteered to be placed in segregation, using small samples sizes, and for being short-term, all of which do not match the current reality of how AS exists in U.S. prisons today.…”
Section: Quantitative Researchmentioning
confidence: 99%